INNOVATIVE SYSTEM FOR MONITORING HEALTH INDICATORS WITH VIRTUAL ASSISTANCE FOR ELDERLY PEOPLE WITH VISUAL LIMITATIONS - JIMENEZ-CORTEZ, CAROLINA (2024)
THE PURPOSE OF THE RESEARCH WAS TO DESIGN A VITAL SIGNS ALERT AND MONITORING SYSTEM WITH VIRTUAL ASSISTANCE THAT IMPROVES CARE FOR OLDER ADULTS WITH VISUAL DISABILITIES. THE METHODOLOGY OF THE STUDY ENCOMPASSED THE APPLIED TYPE OF METHOD WITH AN EXPERIMENTAL RESEARCH DESIGN AND A QUANTITATIVE APPROACH. THE POPULATION STUDIED IS IN THE CONSTITUTIONAL PROVINCE OF CALLAO AND WAS CARRIED OUT ON 10 OLDER ADULTS WITH VISUAL DISABILITIES. THE INFORMATION FROM THE INSTRUMENTS FOR DATA COLLECTION WAS COMPILED, AMONG THE POSITIVE RESULTS OBTAINED WE PRESENT THE RESPONSE OF 10 OLDER ADULTS WITH VISUAL DISABILITIES, WHO VOLUNTARILY PARTICIPATED IN A TEST OF THE USE OF THE PROTOTYPE OF THE VITAL SIGNS MONITORING SYSTEM WITH VIRTUAL ASSISTANCE. THE AVERAGE SCORE OBTAINED IN THIS EVALUATION IS FAVORABLE 4.9, WHICH SHOWS US THAT OUR APPROVAL RATE IS 81.7%. IT IS CONCLUDED THAT THE DESIGN IMPROVES CARE FOR OLDER ADULTS WITH VISUAL DISABILITIES. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.